Occurrence of Cystoisospora spp. and other intestinal parasites in dogs and cats with diarrhea - Simone Morelli; Angela Di Cesare; Donato Traversa; Chiara Astuti; Ilaria Lallone; Costantina N. Tsokana; Donatella Damiani; Melissa Beall; Jesse Buch; Daniela do Amaral Grossi; Sarah Peterson; Gaia Grimaldi; et al. (Veterinary Parasitology, 2025)

Seropositivity for Toxoplasma gondii in cats with clinical signs and living in households with women of childbearing age - Donato Traversa; Simone Morelli; Angela Di Cesare; Mariasole Colombo; Raffaella Iorio; Alessandra Pagliaccia; Cecilia Catalano; Barbara Paoletti; Roberto Brueckmann (Veterinary Parasitology, 2024)

Comparison of diagnostic methods for laboratory diagnosis of the zoonotic tapeworm Dipylidium caninum in cats - Simone Morelli; Angela Di Cesare; Donato Traversa; Mariasole Colombo; Barbara Paoletti; Agnese Ghietti; Melissa Beall; Kristen Davenport; Jesse Buch; Raffaella Iorio; Erica Marchiori; Antonio Frangipane di Regalbono; et al. (Veterinary Parasitology, 2024)

Clinical efficacy of a parasiticide formulation containing eprinomectin, esafoxolaner and praziquantel (NexGard® Combo) in the treatment of natural feline aelurostrongylosis and troglostrongylosis - Angela Di Cesare; Fabrizia Veronesi; Paolo Emidio Crisi; Mariasole Colombo; Simone Morelli; Massimo Vignoli; Giulia Rigamonti; Raffaella Iorio; Eric Tielemans; Frederic Beugnet; Camille Gamblin; Donato Traversa (Veterinary Parasitology, 2024)

Efficacy of a spot-on formulation containing 280 mg/ml fluralaner and 14 mg/ml moxidectin (Bravecto® Plus) in the prevention of cat aelurostrongylosis under field conditions - Angela Di Cesare; Simone Morelli; Nadja Rohdich; Zvezdelina Kirkova; Balázs Capári; Wolfgang Loehlein; Oliver Wolf; Eva Zschiesche; Mariasole Colombo; Chiara Astuti; Donato Traversa (Veterinary Parasitology, 2024)

ENRICH: Multi-purposE dataset for beNchmaRking In Computer vision and pHotogrammetry - Davide Marelli; Luca Morelli; Elisa Mariarosaria Farella; Simone Bianco; Gianluigi Ciocca; Fabio Remondino (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Severe Verminous Pneumonia Caused by Natural Mixed Infection with Aelurostrongylus abstrusus and Angiostrongylus chabaudi in a European Wildcat from Western Balkan Area - Oliver Stevanović; Anastasia Diakou; Simone Morelli; Smiljana Paraš; Igor Trbojević; Drago Nedić; Željko Sladojević; Dragan Kasagić; Angela Di Cesare (Acta Parasitologica, 2019)

Infectious agents after liver transplant: etiology, timeline and patients’ cell-mediated immunity responses - Angela Chiereghin; Evangelia Petrisli; Matteo Ravaioli; Maria Cristina Morelli; Gabriele Turello; Diego Squarzoni; Giulia Piccirilli; Simone Ambretti; Liliana Gabrielli; Antonio Daniele Pinna; Maria Paola Landini; Tiziana Lazzarotto (Medical Microbiology and Immunology, 2017)

Terrestrial laser scanner and geomechanical surveys for the rapid evaluation of rock fall susceptibility scenarios - Giovanni Gigli; Stefano Morelli; Simone Fornera; Nicola Casagli (Landslides, 2014)